2022
DOI: 10.3390/ijms23137398
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Spectrum and Disease Course of DRAM2 Retinopathy

Abstract: Pathogenic variants in DNA-damage regulated autophagy modulator 2 gene (DRAM2) cause a rare autosomal recessive retinal dystrophy and its disease course is not well understood. We present two Slovenian patients harboring a novel DRAM2 variant and a detailed review of all 23 other patients described to date. Whole exome and whole genome sequencing were performed in the two patients, and both underwent ophthalmological examination with a 2-year follow-up. PubMed was searched for papers with clinical descriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
(140 reference statements)
1
8
0
Order By: Relevance
“…This reflected the variability in the RPGR variants and the regional genetic specificity of the RPGR patients. The latter was observed previously for other retinal dystrophy genes in Slovenia; i.e., USH2A [ 46 ], BEST1 [ 47 ], ABCA4 [ 48 ], and DRAM2 [ 49 ]. Reports on small cohorts of specific ethnicities can add important information to the known landscape of genetic variants in specific genes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This reflected the variability in the RPGR variants and the regional genetic specificity of the RPGR patients. The latter was observed previously for other retinal dystrophy genes in Slovenia; i.e., USH2A [ 46 ], BEST1 [ 47 ], ABCA4 [ 48 ], and DRAM2 [ 49 ]. Reports on small cohorts of specific ethnicities can add important information to the known landscape of genetic variants in specific genes.…”
Section: Discussionsupporting
confidence: 78%
“…There have been conflicting reports regarding the association between the location of the variant within the RPGR gene and the disease severity. Some studies reported that variants in the RCC1-like domain (RLD) of the N-terminus resulted in a more severe disease compared with variants in ORF15 [ 15 , 48 , 49 , 50 ], while others did not find any differences between ORF15 and non-ORF15 disease severity based on structural and functional measures [ 54 , 55 ]. On the contrary, ORF15-RP-causing variants were reported to result in better ERG responses and a more intact VF compared with variants in exons 1–14 [ 17 ]; however, the opposite was reported by others [ 18 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rare biallelic DRAM2 variants causing putative loss of DRAM2 function have been associated with retinal dystrophy ( El-Asrag et al, 2015 ; Sergouniotis et al, 2015 ; Birtel et al, 2018 ; Kuniyoshi et al, 2020 ; Krašovec et al, 2022 ). Early in the third decade of life, patients become symptomatic, suffering from maculopathy and progressive central visual loss.…”
Section: Resultsmentioning
confidence: 99%
“…DRAM2 -associated retinopathy, also called cone-rod dystrophy 21 (CORD21), is a rare autosomal recessive IRD caused by coding variants in the DNA-damage Regulated Autophagy Modulator 2 ( DRAM2 ) gene ( El-Asrag et al, 2015 ; Sergouniotis et al, 2015 ; Birtel et al, 2018 ; Abad-Morales et al, 2019 ; Kuniyoshi et al, 2020 ; Krašovec et al, 2022 ). DRAM2 -retinopathy patients are usually asymptomatic in the first 2 decades of life, but then develop progressive central vision loss, associated with characteristic clinical features such as fine white/yellow dots, well-defined atrophic areas in the central retina, and bone-spicule pigmentation in the periphery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation